Studi Komparatif 4P (Penghimpunan, Pendistribusian, Pendayagunaan dan Pelaporan) Zakat di Baznas Jember dan Banyuwangi - Roni Subhan; Imam Turmudi (Al'Adalah, 2019)
BAZNAS (National Amil Zakat Agency) is the official body and the only one formed by the government based on Presidential Decree No. 8 of 2001 which has the duties and functions of collecting and distributing zakat, infaq, and alms (ZIS) at the national level. This study aims to explore the application of 4P (Distribution, Collection, Utilization, and Reporting) in zakat management in BAZNAS Jember and Banyuwangi Regencies. Comparative Study of Zakat management performance measurement in terms of Fayol's management principles theory. The sample selection method is judgment sampling while the data analysis method used is descriptive qualitative analysis and comparison. The results of the study show that each BAZNAS in the Jember and Banyuwangi districts has carried out zakat management activities with 4P elements (Distribution, Collection, Utilization, and Reporting). The Amil Zakat Agency in Banyuwangi is better at implementing the four elements of zakat management including adequate internal controls and controls that will be held within a certain time.